Development of Early Landslide Detection Tool as Optimization of Disaster Mitigation Understanding for Early Childhood in Wonosobo - Af'idah, Nabila Zakiyyatul; Waluyo, Edi (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
Early childhood is a crucial period with immense potential and high vulnerability to natural disasters. In Wonosobo Regency, landslides pose a serious threat, necessitating concrete efforts to enhance the preparedness of young children. This study aims to develop an early landslide detection tool to improve disaster mitigation understanding among early childhood children. The research method employed is Research and Development (R&D) using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques include observation, interviews, and documentation, which were subsequently analyzed. The study results indicate that the developed early detection tool is highly feasible, with an expert media evaluation score of 100%, making the product suitable for further testing. Trials showed that this tool could provide fast and accurate warnings about potential landslides, significantly enhancing preparedness and disaster mitigation understanding among young children in the Wonosobo Regency. The implications of this research highlight the importance of integrating early detection technology into disaster mitigation education, which can improve the safety and understanding of young children regarding future disasters.